Korelasi agama dengan stratifikasi sosial terhadap intensitas partisipasi individu dalam ibadah dan peran di masyarakat - Rahmawati, Ainia Fikri (Maliki Interdisciplinary Journal, 2024)
The differences that exist in social life in the world cause the grouping of people in several categories. These groupings cause variations in life in the form of the phenomenon of social stratification. This research aims to examine the relationship between religion and social stratification of individuals in terms of worship and society. This research is a type of qualitative research with descriptive methods through a sociological approach. Data analysis in this study used Miles and Huberman’s interactive analysis technique. The results found that there are forms of social startification in religion in Christian, Hindu and Islamic communities. There are similarities and differences in aspects to determine human position in religion and social stratification. In this case, religion plays a role in embedding social startification of individuals in society. Vice versa, social stratification also affects the intensity of a person’s fulfillment of worship. Religion and social stratification also influence a person’s level of involvement in society.